COP 21 and Economic Theory: Taking Stock - Henry Tulkens (Fondazione Eni Enrico Mattei (FEEM), 2016)
The texts of the COP 21 Decision and its Annex are scrutinized from the particular point of view of the extent to which economic theoretic concepts can be considered to inspire them. While this is shown to be partially the case in some of the intentions, the texts themselves contain more diplomatically formulated promises than implementation of mainstream well established economic concepts.
Keywords: F02; F55; H40; H87; Q52; Q54; 330; Economic and Game Theory Concepts; International Climate Agreements; Voluntary Cooperation; Greenhouse Gas Emissions; Transfers